AGREEABLENESS SEBAGAI MODERATOR HUBUNGAN EKSPOSUR TAYANGAN ANTISOSIAL DAN PERUNDUNGAN-SIBER PADA REMAJA - Nisa Fitriani (Psyche: Jurnal Psikologi, 2020)
This study examined the moderating effect of agreeableness on the relation between exposure of antisocial media and cyberbullying. The subjects of the research were 293 junior high school students 12-16 years old (M = 13,58; SD = 0,74) in Malang City. Instruments used were The Cyberbullying Questionnaire, Content-based Media Exposure Scale, and The Big Five Inventory. The result indicated that agreeableness is moderator exposure of antisocial media and cyberbullying (β = -0,155; p = 0,006). Correlation between exposure of antisocial media and cyberbullying is stronger in adolescents with low levels of agreeableness than adolescents with high agreeableness.